Environmental Drivers of Holocene Forest Development in the Middle Atlas, Morocco - Campbell, Jennifer F. E.; Fletcher, William J.; Joannin, Sebastien; Hughes, Philip D.; Rhanem, Mustapha; Zielhofer, Christoph (Frontiers in Ecology and Evolution, 2017)
In semi-arid regions subject to rising temperatures and drought, palaeoecological insights into past vegetation dynamics under a range of boundary conditions are needed to develop our understanding of environmental response to climatic changes. Here, we present a new high-resolution record of vegetation history and fire activity spanning the last 12,000 years from Lake Sidi Ali in the southern Middle Atlas Mountains, Morocco. The record is underpinned by a robust AMS radiocarbon and 210Pb/137Cs chronology and multi-proxy approach allowing direct comparison of vegetation, hydroclimate and catchment tracers. The record reveals the persistence of steppic landscapes until 10,340 cal yr BP, prevailing sclerophyll woodland with evergreen Quercus until 6300 cal yr BP, predominance of montane conifers (Cedrus and Cupressaceae) until 1300 cal yr BP with matorralization and increased fire activity from 4320 cal yr BP, and major reduction of forest cover after 1300 cal yr BP. Detailed comparisons between the pollen record of Lake Sidi Ali (2080 m a.s.l.) and previously published data from nearby Tigalmamine (1626 m a.s.l.) highlight common patterns of vegetation change in response to Holocene climatic and anthropogenic drivers, as well as local differences relating to elevation and bioclimate contrasts between the sites. Variability in evergreen Quercus and Cedrus at both sites supports a Holocene summer temperature maximum between 9000 and 7000 cal yr BP in contrast with previous large-scale pollen-based climate reconstructions, and furthermore indicates pervasive millennial temperature variability. Millennial-scale cooling episodes are inferred from Cedrus expansion around 10,200, 8200, 6100, 4500, 3000 and 1700 cal yr BP, and during the Little Ice Age (400 cal yr BP). A two-part trajectory of Late Holocene forest decline is evident, with gradual decline from 4320 cal yr BP linked to synergism between pastoralism, increased fire and low winter rainfall, and a marked reduction from 1300 cal yr BP, attributed to intensification of human activity around the Early Muslim conquest of Morocco. This trajectory, however, does not mask vegetation responses to millennial climate variability. The findings reveal the sensitive response of Middle Atlas forests to rapid climate changes and underscore the exposure of the montane forest ecosystems to future warming.